2020
DOI: 10.1111/jvh.13436
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection mortality trends according to three definitions with special concern for the baby boomer birth cohort

Abstract: Cause-specific mortality data are the most commonly used health data for monitoring changes in the burden of disease at the national level. Several studies have used the national mortality data to illustrate the changes in mortality from hepatitis C virus (HCV) infection in the United States. 1-6 The official published mortality data 7 were compiled according to the underlying cause of death (UCOD), which is defined as '(a) the disease or injury which initiated the train of morbid events leading directly to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…These medications were introduced in Brazil in 2013, and, since then, the Brazilian Ministry of Health has updated its clinical protocol and therapeutic guidelines with the inclusion of new medications and expanded access to treatment, which, since 2017, has included all diagnosed cases of chronic hepatitis C in Brazilian territory [ 34 ]. It is important to note that the present study only considered those whose underlying cause of death was acute (B 17.1) or chronic (B 18.2) hepatitis C. Therefore, the causes of death recorded as a complication or aggravation associated with HCV, such as liver cirrhosis or liver cancer, may cause an underestimation of the HCV mortality rate found here [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…These medications were introduced in Brazil in 2013, and, since then, the Brazilian Ministry of Health has updated its clinical protocol and therapeutic guidelines with the inclusion of new medications and expanded access to treatment, which, since 2017, has included all diagnosed cases of chronic hepatitis C in Brazilian territory [ 34 ]. It is important to note that the present study only considered those whose underlying cause of death was acute (B 17.1) or chronic (B 18.2) hepatitis C. Therefore, the causes of death recorded as a complication or aggravation associated with HCV, such as liver cirrhosis or liver cancer, may cause an underestimation of the HCV mortality rate found here [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this national population-based study indicate that a persistent decline in the cryoglobulinemia mortality rates from 1999 to 2010, followed by a mild increase from 2010 to 2014, and then an abrupt decline from 2014 to 2018. The study has indicated high prevalence of HCV among baby boomers born 1945–1964 and resulted in the increase of HCV mortality since 2000 [ 13 , 14 ]. The cryoglobulinemia mortality for middle-age adults aged 55–64 years increased since early 2000s (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 C) and for older adults aged ≥ 65 years increased since 2010 (Fig. 1 D) corresponding to age-specific HCV mortality rates of baby boomers born 1950–1959 and 1945–194, respectively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age-speci c cryoglobulinemia mortality trend patterns correspond with the age-speci c HCV mortality trend patterns. 13 The age differences in mortality trend patterns re ect the aging and dying of "baby boomers" (born between 1945 and 1965 in the United States) with a high prevalence of HCV. 14 The increased cryoglobulinemia mortality among middle-age adults aged 55-64-years from the early 2000s and older adults aged 65-years and above from the late 2000s can be mainly attributed to the aging of "baby boomers.…”
Section: Discussionmentioning
confidence: 99%